Robotic-Assisted Laparoscopic Resection of Tailgut Cysts - Rompen, Ingmar F. (JSLS, 2021)
INTRODUCTION: Tailgut cysts are rare remnants of the embryological hindgut. Resections are difficult to perform due to the narrow and delicate presacral space where they are usually located. Many different approaches have been described, but to date, no studies have been performed concerning robotic assisted surgery for this entity. Therefore, we conducted a retrospective analysis to evaluate the feasibility and outcome parameters of the robotic anterior approach for resection of tailgut cysts and to compare our results with available literature. MATERIAL AND METHODS: Data was retrospectively obtained from hospital records of all patients who underwent robotic assisted resection of tailgut cysts between January 1, 2017 and June 30, 2020. Outcomes include baseline characteristics, pre-operative radiological workup, operative time, intra- and postoperative complications, and histopathological results. RESULTS: Between January 1, 2017 and June 30, 2020, five patients underwent robotic resection of tailgut cysts. All patients were female and mean age was 47.2 years (range 31.6–63.1 years). Only one patient reported to have local symptoms that could be attributed to the tailgut cyst. Median tumor size was 42 mm (range 30–64 mm). There was no conversion and median operating time was 235 minutes (range 184–331 minutes). Four patients had additional procedures. Intra- and postoperative complications included one intra-operative injury of the rectal wall, which was immediately oversewn, and one postoperative presacral hematoseroma with mild neurological symptoms. None of the specimens showed signs of malignant transformation in histopathological workup. CONCLUSION: This retrospective analysis shows that robotic resections of tailgut cysts are feasible and safe. Regarding the localization of tailgut cysts in the presacral space, the robotic assisted anterior approach is excellently suited, especially if the cysts are localized above the levator muscle. Longer operative times and higher material costs are outweighed by precise and safe preparation with a robotic platform in this delicate region and confined space. We recommend the robotic assisted anterior approach for the resection of tailgut cysts and retrorectal lesions in general.